2012
DOI: 10.1093/aob/mcs185
|View full text |Cite
|
Sign up to set email alerts
|

Cytotype diversity in the Sorbus complex (Rosaceae) in Britain: sorting out the puzzle

Abstract: Flow cytometry results obtained have proved useful in shedding light on the taxonomy of several controversial taxa and in confirming the presence of cytoypes which occur at very low frequencies. Notably, the coexistence of several cytotypes in Sorbus populations has probably been facilitated by the overlapping distribution of many of the species studied, which might also explain the high incidence of potential hybrid apomictic polyploids. These results will provide a solid baseline for molecular research aimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 31 publications
5
91
0
Order By: Relevance
“…In this case, chromosome counts have been carried out on some of the Sorbus taxa with diploid (2n534), triploid (2n551), and tetraploid (2n568) individuals found among the genus (Bailey et al, 2008). The use of flow cytometry to estimate the relative DNA content, and hence to infer DNA ploidies, has recently been used to analyse the cytotype diversity in a large-scale survey of British Sorbus species (Pellicer et al, 2012). This study revealed the high incidence of polyploidy in the genus (3x, 4x, and 5x), while also confirming the constancy of diploid cytotypes in parental taxa in Britain, including all samples of S. torminalis evaluated.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…In this case, chromosome counts have been carried out on some of the Sorbus taxa with diploid (2n534), triploid (2n551), and tetraploid (2n568) individuals found among the genus (Bailey et al, 2008). The use of flow cytometry to estimate the relative DNA content, and hence to infer DNA ploidies, has recently been used to analyse the cytotype diversity in a large-scale survey of British Sorbus species (Pellicer et al, 2012). This study revealed the high incidence of polyploidy in the genus (3x, 4x, and 5x), while also confirming the constancy of diploid cytotypes in parental taxa in Britain, including all samples of S. torminalis evaluated.…”
Section: Introductionsupporting
confidence: 59%
“…Sorbus leyana Wilmott . This complex array of morphologically diverse taxa arose from hybridisation events involving crossings between the diploid species and other polyploid apomicts , resulting in a taxonomically intricate polyploid network (Pellicer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High diversity of ploidy levels is not unusual in members of Rosaceae, among which at least 32 of 85 genera show polyploidy , and this has been studied in detail in, for example, Crataegus Lo et al 2010) and Sorbus (Robertson et al 2010;Pellecier et al 2012). On the other hand, hexaploids are not common in the family, having so far been recorded only in Cotoneaster, Crataegus, Malus , and Polylepis (Segovia et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…: 0.79±0.01, and 1.05±0.011 were detected. According to Pellicer et al (2012), the genome sizes within the genus Sorbus are relatively well conserved among different lineages, both in diploids and polyploids. As we previously calibrated the ratio of 0.52 with a diploid chromosome count (Meyer et al 2014) the measured DNA-ploidy levels correspond to tri-and tetraploidy (Electronic Appendix 3).…”
Section: Dna-ploidymentioning
confidence: 99%